Data privacy rights and bankers’ business interests in Nigeria : reflections on opportunities, challenges and legal reforms - Abdulkadir, Abdulkadir Bolaji; Sambo, Abdulfatai Oladapo (Penerbit Universiti Kebangsaan Malaysia, 2022)
Data (Personal Information), the oil of the digital age, has taken the centre stage due to increasing use of technology in almost all human endeavours. This is not unconnected to the large scale unlawful usage of people’s data by cyber criminals. This is particularly the situation in banking sector. Yet, Nigeria seems to be lagging behind in its efforts to protect this right through effective legislative framework to protect individual information from unlawful and unauthorised possession or use. Nonetheless, efforts are on top gear at the global level to stem this ugly tide. Therefore, this paper seeks to investigate the Data Protection challenges in the Nigerian banking sector with critical analysis of the current legal framework for the protection of personal information in the Nigerian banking sector. Using doctrinal methods where primary and secondary sources of legal materials were subjected to content analysis, the study found that legal architecture on data protection in Nigeria is weak and ineffective in stemming the tide of the challenges posed by data challenges. It was also concluded that effective legal framework on data protection is necessary for the enjoyment of the opportunities of this digital age. The study thus recommended that there should be effective data protection legislation in Nigeria particularly in the banking sector that would protect data privacy as well as the legitimate business interests of bankers.